Enhancement of dimensional accuracy of micro features by applying parametric error compensation to the miniaturised machine tool. (1st November 2010) - Samuel, G.L.; Yang, Seung-Han
Imperfections in the miniaturised machine tool will affect dimensional accuracy of micro components. It is necessary to measure these errors and apply compensation to improve their performance. In the present work, parametric errors of a miniaturised vertical milling machine were measured using capacitance sensors and the data is analysed using computational geometric techniques. Kinematic model of micro machine is developed and the error compensation is applied. To investigate the effect of error compensation on the dimensional accuracy of components, experiments were conducted while the machine tool is operating under point to point (PTP) control and continuous control. Machined profiles before and after compensation were inspected using a CMM and found that the profiles machined after applying compensation had better dimensional accuracy. This is due to the improvement of tool positioning accuracy after compensation. The details of measurement, modelling, error compensation, experiments and the results are presented in this paper.